OPTIMIZATION OF LAPAROSCOPIC INTERVENTION TACTICS FOR MECKEL'S DIVERTICULUM IN CHILDREN (World Bulletin of Public Health, 2024)
The article discusses the effectiveness of laparoscopic interventions (LI) for Meckel's diverticulum (MD) in children. A total of 174 patients were examined from 2006 to 2021. The pathology was observed mainly in children under 3 years of age (38.8%), in 58% of cases the patients were hospitalized with suspected appendicitis. The indication for laparoscopy was the picture of acute abdomen and gastrointestinal bleeding. 98 laparoscopies and 76 laparotomies were performed, with an increase in LI and a decrease in conversions, i.e. the transition from laparoscopies to open interventions, noted. When performing KD, there is a decrease in blood loss, relief of pain, rapid normalization of temperature, early activation of patients, and the duration of hospitalization decreased from 9 to 3 days. The results of the study show the high effectiveness of laparoscopic interventions in children.
Keywords: Meckel's diverticulum; children; laparoscopy; bleeding